2010
DOI: 10.3109/02713680903548970
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Markers in Patients with Primary Open-Angle Glaucoma

Abstract: Increased levels of aqueous humor GPO, SOD, and MDA may be associated with POAG. In addition, they may be useful antioxidant enzyme levels in aqueous humor of POAG patients as a result of glaucoma disease and not a cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 15 publications
2
112
0
2
Order By: Relevance
“…But, about serum superoxide dismutase, the present study reported that it increased significantly in group B of untreated POAG patients and also in group C of patients of POAG under treatment in comparison to the control group, in agreement with Erdurmuş et al (2011) [11], who reported the same results, in addition Ghanem et al (2010) [19], who found that superoxide dismutase increased significantly in aqueous humor in patient of POAG. But, Majsterek et al (2011) [14], reported that SOD was decreased in patients with POAG as it is considered anti-oxidant factor, the present study and the previous two studies that agreed in their results of increase of SOD in patients of POAG explained this increase to be a compensatory mechanism for anti-oxidant activity against [14], who stated that MDA increased in cases of POAG as an oxidative stress biomarker.…”
Section: Discussionsupporting
confidence: 81%
“…But, about serum superoxide dismutase, the present study reported that it increased significantly in group B of untreated POAG patients and also in group C of patients of POAG under treatment in comparison to the control group, in agreement with Erdurmuş et al (2011) [11], who reported the same results, in addition Ghanem et al (2010) [19], who found that superoxide dismutase increased significantly in aqueous humor in patient of POAG. But, Majsterek et al (2011) [14], reported that SOD was decreased in patients with POAG as it is considered anti-oxidant factor, the present study and the previous two studies that agreed in their results of increase of SOD in patients of POAG explained this increase to be a compensatory mechanism for anti-oxidant activity against [14], who stated that MDA increased in cases of POAG as an oxidative stress biomarker.…”
Section: Discussionsupporting
confidence: 81%
“…Unstable free radical species then attack cellular components causing damage to lipids, proteins, and DNA that can initiate a chain of reactions resulting in the onset of a variety of diseases, 17 including GON. [18][19][20][21] In fact, recent studies have suggested that oxidative damage constitutes an important pathologic step in inducing and maintaining the degeneration of the trabecular meshwork, optic nerve, and RGCs. Gherghel et al, for example, reported that glaucoma patients exhibit low levels of circulating glutathione, suggesting compromised oxidative defence.…”
Section: Introductionmentioning
confidence: 99%
“…The Val isoform of SOD2 has been suggested that may lead to a decreased resistance against ROS produced in the mitochondria and to oxidative damage of proteins caused by less efficient SOD2 transport into the mitochondria [34]. Several studies suggested that a significant increase in oxidative stress may play a role in the pathogenesis of POAG [35,36].…”
Section: Discussionmentioning
confidence: 99%